Variations in the vertical component of the electrotelluric field at the Yuzhno-Sakhalinsk geophysical test site in 2024 - Stovbun, Nikolai S.; Zakupin, Alexander S.; Bogomolov, Leonid M.; Kostylev, Dmitry V.; Dudchenko, Ilya P.; Gulyakov, Sergey A. (Геосистемы переходных зон, 2025)
In 2024, the Institute of Marine Geology and Geophysics of the Far Eastern Branch of the Russian Academy of Sciences started continuous measurements of the vertical component of the electrotelluric field (ETF), which were integrated into the previously organized monitoring of the horizontal components of the ETF. The vertical component of the ETF is measured by the potential difference between metal plates located in the ground, one above the other, at a depth of about 2 m. Two systems of plates were installed at the Yuzhno Sakhalinsk geophysical test site (on the territory of IMGG FEB RAS) and were connected to an analog-to-digital converter (ADC). The aim of the study is to identify and analyze variations in the vertical ETF that may be associated with the geological deformation and variations in seismicity. In the first year of measurements of the vertical component of the ETF, 4 periods with an abnormally high level of field strength were identified compared to the average value for the observation period: maximum by 35 times, minimum by 5 times. In total, these periods occupy about half of the entire registration time; it was during these periods that 80% of all earthquakes in the southern part of Sakhalin Island occurred over 11 months of 2024 (24 events out of 30). For the horizontal components of the ETF, no such significant anomalies were observed as for the vertical one. Obtained results indicate that changes in the vertical component of the ETF may reflect variations in seismic activity in the near field. These changes can presumably be considered a sign of earthquake activity near the measurement point.